Logos’ Centrality and Expression in Martyria as a Superior Form of Dialogue - Vasilică Bîrzu (Religions, 2021)
This paper describes some motivations and outlines some limits regarding the possibility and necessity of interreligious, interconfessional, and interideological dialogue, in an attempt to improve our understanding of Orthodox Christianity’s role in these important aspects of domestic and foreign politics. This study aims to resolve the divergent opinions that exist in the Orthodox Church regarding the possibility of remaining in this kind of dialogue. The ancient philosophical mode of dialogue and the modern one are analyzed: dialogue as debate and negotiation. The study begins from the analysis of some technical terms describing the social and spiritual dimensions of dialogue; from the perspective of these spiritual and social dimensions, the possibilities, the potential positive results, and the risks of remaining in dialogue with someone of another confession, belief, or ideology are analyzed. It reveals the evolution of the dialogue’s content, its enrichment with the spiritual dimensions of martyria and exomologesis, and the efficient centrality of the Logos in it, as suggested by the etymological definition of dialogue. It also emphasizes the necessity of a deep understanding of all these spiritual dimensions of dialogue for achieving efficient and fruitful communication with representatives of other social or religious groups. This communication can be seen as a guarantee of peace and social stability.